Chemoprevention of cancer: a clinical update - Senn, Hansjörg; Costa, Alberto; Jordan, V. Craig (Springer, 1999)
This volume contains part of the papers given at the second annual conference of the newly founded International Society of Cancer Chemoprevention held in August 1997 in St. Gallen, Switzerland. Pharmacologic intervention in human carcinogenes is in its very infancy, and internationally coordinated efforts to fight the evolution of human cancers are only now taking shape. This is one of the first efforts to unite experts of all major groups and centers worldwide in the highly fascinating and thought-provoking field of chemoprevention of cancer, especially of the breast, colon and prostate